The mechanical and interfacial properties of concrete prepared by recycled aggregates with chloride corrosion media. (3rd May 2021) - Tian, Yaogang; Jiang, Jing; Wang, Shuaifei; Yang, Tingting; Qi, Lin; Geng, Jiuguang
Highlights: The recycled aggregates (RA) were soaked in 3%, 5% and 7% NaCl solution for 120 d. The Cl − introduced by RA is mainly distributed around interfacial transition zones. The Cl − diffused was increased with the increase of RA's corrosion degree. The properties of concrete improved in early age as the increase of Cl − content. Abstract: Recycled aggregates (RA) prepared by concrete suffering a long-term service inevitably carried chloride corrosion media, which would lead to some effects on performance of recycled aggregate concrete (RAC) – concrete prepared by RA- from the inside. Hence, this research evaluated the effect of RA with different corrosion degree, which were soaked in 3%, 5% and 7% NaCl solution for 120 days respectively, on the mechanical properties of RAC and analyzed the dissolution characteristics of chloride element in cement mortar by SEM-EDS, moreover, the performance change of interfacial transition zones (ITZs) was also studied via microhardness test and micro tests (SEM, EDS and XRD). The results showed that Cl − carried by RA partly diffused into the cement mortar, while most of them distributed in the ITZs, and the Cl − accelerated the cement hydration and produced a small amount of Friedel's salt to optimize the pore structure, which did well in improving the strength and the performance of ITZs between old mortar and new mortar (OM-NM), old aggregate and new mortar (OA-NM), in early stage. However, with the increase of RA's corrosion degree and concrete's ages, the amount of internal corrosion products, Friedel's salt etc., would be more, and it caused the later strength reduction and the interfacial performance in OM-NM and OA-NM to became poor.